2021
DOI: 10.1108/imefm-08-2020-0408
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian Islamic moral incentives in credit card debt repayment: a feature selection using various data mining

Abstract: Purpose Despite the practice of credit card services by Islamic financial institutions (IFIs) is debatable, Islamic banks (IBs) have been offering this product. Both Muslim and non-Muslim customers have subscribed to the products. Thus, it is critical to analyse the strategy of IBs’ moral messages in reminding their Muslim and non-Muslim customers to repay their credit card debts. This paper aims to investigate this issue in Indonesia using data mining via machine learning. Design/methodology/approach This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…Text mining is part of data mining (in big data analytics) to extract information from semi or unstructured text data for discovering knowledge and generating new facts through categorisation, clustering and visualisation of the data (Caraka et al , 2022; Cheerkoot-Jalim and Khedo, 2020; Hashimi et al , 2015; Hassan et al , 2021; Hudaefi et al , 2022b; Usai et al , 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Text mining is part of data mining (in big data analytics) to extract information from semi or unstructured text data for discovering knowledge and generating new facts through categorisation, clustering and visualisation of the data (Caraka et al , 2022; Cheerkoot-Jalim and Khedo, 2020; Hashimi et al , 2015; Hassan et al , 2021; Hudaefi et al , 2022b; Usai et al , 2018).…”
Section: Methodsmentioning
confidence: 99%
“…From the above presentation, most research in ISF is carried out with a theoretical approach. Many researchers have concluded that Islamic social security is a financial system based on morals and ethics (Caraka et al, 2022). However, researchers have not mathematically calculated ISF's moral and ethical components.…”
Section: Research Agendamentioning
confidence: 99%
“…The analysis provides a set of clusters that explains meaningful hierarchies in which each cluster is different, and the objects within each cluster are approximately comparable to each other (Zhao et al, 2005). In previous studies, hierarchical clustering at least has been used by Buana et al (2020), Caraka et al (2021), to cluster similar information from data texts. Under the lens of hierarchical clustering, this paper aims to answer the following research question two:…”
Section: Knowledge Gapmentioning
confidence: 99%